2020
DOI: 10.1111/gcb.15035
|View full text |Cite
|
Sign up to set email alerts
|

Cold range edges of marine fishes track climate change better than warm edges

Abstract: Species around the world are shifting their ranges in response to climate change. To make robust predictions about climate‐related colonizations and extinctions, it is vital to understand the dynamics of range edges. This study is among the first to examine annual dynamics of cold and warm range edges, as most global change studies average observational data over space or over time. We analyzed annual range edge dynamics of marine fishes—both at the individual species level and pooled into cold‐ and warm‐edge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 81 publications
5
82
1
Order By: Relevance
“…The application of a consistent methodology and dataset for developing comparable range shift analyses was a crucial aspect of this study as methodological difference have been found to explain approximately 22% of variation in rates of climatedriven redistributions (Brown et al, 2016). For example, studies utilising continuous and consistent time series more accurately quantify rates of species redistributions than estimates based on infrequent data that may confound short-term variability with long-term trends (Brown et al, 2016;Fredston-Hermann et al, 2020). Therefore, our range shift estimates based on monthly predictions of species' core habitats over 21 years (i.e., n = 252 per species) are likely to be more robust to shortterm oceanographic variability occurring during this period than, for example, analyses based on seasonal or annual data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of a consistent methodology and dataset for developing comparable range shift analyses was a crucial aspect of this study as methodological difference have been found to explain approximately 22% of variation in rates of climatedriven redistributions (Brown et al, 2016). For example, studies utilising continuous and consistent time series more accurately quantify rates of species redistributions than estimates based on infrequent data that may confound short-term variability with long-term trends (Brown et al, 2016;Fredston-Hermann et al, 2020). Therefore, our range shift estimates based on monthly predictions of species' core habitats over 21 years (i.e., n = 252 per species) are likely to be more robust to shortterm oceanographic variability occurring during this period than, for example, analyses based on seasonal or annual data.…”
Section: Discussionmentioning
confidence: 99%
“…Determining which species are most likely to undergo climate-driven range shifts, and assessing the rates at which these changes are occurring, is essential for managing the consequences for ecosystems and human wellbeing (Pecl et al, 2017;Bonebrake et al, 2018). However, rates of redistribution among marine taxa are considerably variable (Pinsky et al, 2013;Poloczanska et al, 2016;Fredston-Hermann et al, 2020), challenging the capacity of scientists and managers to develop adaptation strategies that are applicable to broad groups of species (Fogarty et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, recruitment and year-class strength can be strongly controlled by environmental conditions in the winter months [ 11 , 17 19 ]. Furthermore, species assemblages respond rapidly to winter temperature and as such, it is likely important for explaining biogeography and range shifts in the context of global climate change [ 20 22 ]. Warming winter water temperatures in response to anthropogenic climate change may enable the poleward range expansion of many temperate species.…”
Section: Introductionmentioning
confidence: 99%
“…Cold range edges have been shown to closely track how marine fishes respond to climate change 33 . The center of gravity of the cold edge (t lat ) of the continuous thermal suitability model varied considerably from 1982 to 2019.…”
Section: Resultsmentioning
confidence: 99%